Aplikasi Permainan Tradisional Mapoh-Pohan Sebagai Metode Simulasi Pembelajaran Agama Hindu Dalam Meningkatkan Minat Belajar Siswa Kelas IV Di SD Negeri 5 Sumerta Denpasar - Ni Luh Candra Erawati; I Wayan Lali Yogantara; I Nyoman Kiriana (Cetta: Jurnal Ilmu Pendidikan, 2019)
Lack of student interest in learning causes problems in the learning process. In dealing with this problem Sumerta 5 State Elementary School Denpasar applied traditional mapoh-pohan as a method of simulation of Hindu learning for class IV. The results showed (1) the form of traditional game mapoh-pohan as a learning method similar to the game of dragon snake but different in terms, language and song used (2) This method has several functions, namely: 1) educational function: increase participation, interest and achievement student learning, 2) social functions: improving students' social skills and teacher and student interpersonal relationships, 3) cultural preservation and 4) recreational media. (3) The values ​​contained in this method are: the formation of character (sportsmanship, honesty, independence, fieldwork, discipline and togetherness). Besides that, it also contained the values ​​of Hinduism, namely the cultivation of the teachings of chess paramita, and the teachings of satya.